Inventorying geological heritage in large territories : a methodological proposal applied to Brazil - Lima, Flávia (2010)
An adequate management of geological heritage by national and regional authorities presupposes the existence of a solid geosites inventory. Unfortunately, this is not the case for many countries. Most often, there is no national inventory at all or the method and criteria used to assess geosites was not adequate. This paper makes an overview of the strengths and weaknesses of the most common procedures to produce a geosite inventory and proposes a methodology particularly adapted for large territories such as Brazil. Nevertheless, this methodological approach can be easily adapted to any other geographical or geological setting, promoting the characterization and conservation of the world's geological heritage.